2018
DOI: 10.7150/thno.24015
|View full text |Cite
|
Sign up to set email alerts
|

Cascade-amplifying synergistic effects of chemo-photodynamic therapy using ROS-responsive polymeric nanocarriers

Abstract: The simple integration of chemotherapeutic drugs and photosensitizers (PSs) into the same nanocarriers only achieves a combination of chemo-photodynamic therapy but may not confer synergistic effects. The boosted intracellular release of chemotherapeutic drugs during the photodynamic therapy (PDT) process is necessary to achieve a cascade of amplified synergistic therapeutic effects of chemo-photodynamic therapy.Methods: In this study, we explored an innovative hyperbranched polyphosphate (RHPPE) containing a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 46 publications
2
78
0
Order By: Relevance
“…US exposure also significantly increased the fluorescence of IR780 from the IR780/PTL‐NPs in an intensity‐dependent manner compared to the nonirradiated nanoparticles (Figure D), indicating that IR780 was released from IR780/PTL‐NPs. This is consistent with a previous report showing that fluorescent molecules loaded on nanoparticles undergo quenching occurs due to local accumulation . Transmission electron microscopy (TEM) (Figure E,F) and DLS (Figure S3, Supporting Information) showed that US irradiation had a negligible impact on the morphology of PTL‐NPs, but resulted in the disintegration of IR780/PTL‐NPs, likely due to the ROS‐triggered cleavage of the TL bonds as described.…”
Section: Resultssupporting
confidence: 91%
“…US exposure also significantly increased the fluorescence of IR780 from the IR780/PTL‐NPs in an intensity‐dependent manner compared to the nonirradiated nanoparticles (Figure D), indicating that IR780 was released from IR780/PTL‐NPs. This is consistent with a previous report showing that fluorescent molecules loaded on nanoparticles undergo quenching occurs due to local accumulation . Transmission electron microscopy (TEM) (Figure E,F) and DLS (Figure S3, Supporting Information) showed that US irradiation had a negligible impact on the morphology of PTL‐NPs, but resulted in the disintegration of IR780/PTL‐NPs, likely due to the ROS‐triggered cleavage of the TL bonds as described.…”
Section: Resultssupporting
confidence: 91%
“…It is worth mentioning that all ROS-responsive mechanisms eventually depend on a biological trigger because their working mechanism depends on the oxygen content in the tissue, and they are ineffective in hypoxic regions (Chen et al, 2015). In some cases, the ROS generation is catalyzed directly by the nanoparticles, that due to the properties of their synthesis material, can activate other features of the carriers like payload release (Sun et al, 2018).…”
Section: Ros-responsive Theranosticsmentioning
confidence: 99%
“…For this reason, the carriers needed to generate ROS as well as being sensitive to these chemical species. To this goal, Sun et al (2018) developed nanoparticles of pegylated polyphosphate crosslinked with a thioketal linker via (A2 + B3) type polycondensation. The carriers were loaded with the photosensitizer Ce6 and DOX.…”
Section: Ros-responsive Theranosticsmentioning
confidence: 99%
“…Kim, Jo, et al (2018). Copyright 2018 Wiley) PEGylated hyperbranched polyphosphate (abbreviated as RHPPE) with a thioketal cross-linker, which can induce drug burst release during photodynamic therapy (PDT; Sun et al, 2018). The RHPPE loaded with Ce6 and DOX, simultaneously.…”
Section: Biological-responsive Nanomedicinementioning
confidence: 99%